2021
DOI: 10.1111/are.15481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing dietary soybean meal with pumpkin (Cucurbita pepo) seed cake on growth, feed utilization, haematological parameters and fatty acid composition of mirror carp (Cyprinus carpio)

Abstract: In recent years, aquaculture has dramatically increased concomitant with the global demand for aquatic species (Dawood et al., 2020), with fish feed being the greatest single cost item in aquaculture, accounting for approximately 50% of the total operating costs in intensively reared fish (Ayyat et al., 2021). The increasing demand for fish meal and soybean meal, which are used as protein sources in aquatic feed, as well as the market price increases and fluctuations have caused the aquaculture industry to see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…VSI and HSI showed significant differences in favor of PSC inclusion compared to the control. Our findings contradicted those of Sezgin and Aydın [17], who concluded that PSC had no significant influence on HSI or VSI. However, our result could be explained by several studies, including those of Caili et al [39], Nkosi et al [40], Bardaa et al [16], Musthafa et al [41], and Salehi et al [14], which suggest that the observed improvements in VSI and HSI in tilapia fed with diets containing PSC are likely due to a complex interplay of metabolic processes influenced by the nutritional composition of the feed.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…VSI and HSI showed significant differences in favor of PSC inclusion compared to the control. Our findings contradicted those of Sezgin and Aydın [17], who concluded that PSC had no significant influence on HSI or VSI. However, our result could be explained by several studies, including those of Caili et al [39], Nkosi et al [40], Bardaa et al [16], Musthafa et al [41], and Salehi et al [14], which suggest that the observed improvements in VSI and HSI in tilapia fed with diets containing PSC are likely due to a complex interplay of metabolic processes influenced by the nutritional composition of the feed.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study corroborate those of Caili et al [39], who found that pumpkin seeds could efficiently reduce serum triglyceride levels and cholesterol. Similarly, Sezgin and Aydın [17] found that increasing the inclusion level of PSC in mirror carp (Cyprinus carpio) diets led to a decrease in both cholesterol and triglyceride levels, with a continued effect on cholesterol until reaching 100% inclusion. This notable reduction could be attributed to PSC's phytosterol bioactive components, which might affect both the expression levels of genes related to cholesterol and lipid metabolism and the activity of hepatic enzymes [17,43].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Due to the increasing global population, increasing production in the animal sector is essential for healthy nutrition (FAO, 2020). Common carp, Cyprinus carpio , is one of the most important freshwater fish species in the world, reared either semi‐intensively or intensively (Sezgin & Aydın, 2021). In the developing world where resources are scarce, common carp is an economical and sustainable food source.…”
Section: Introductionmentioning
confidence: 99%